2021
DOI: 10.3390/medicina57070723
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Prothrombotic Gene Variants in Patients with Acute Ischemic Stroke and with Transient Ischemic Attack

Abstract: Background and objectives: ischemic stroke (IS) is among the most frequent causes of death worldwide; thus, it is of paramount relevance to know predisposing factors that may help to identify and treat the high-risk subjects. Materials and Methods:we tested nine variants in genes involved in thrombotic pathway in 282 patients that experienced IS and 87 that had transient ischemic attacks (TIA) in comparison to 430 subjects from the general population (GP) of the same geographic area (southern Italy). We includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…However, it should be recognized that none of the subjects were carriers for any mutations definitively associated with an increased pro-thrombotic risk (such as Factor II G20210A and Factor V G1691A) [23]. On the other hand, the genetic variants identified are not rare in the general population: the double heterozygosity (677 TC/1298 AC) of MTHFR has a frequency of about 34%, while the 1289 CC genotype is present in 9.4% of subjects [52], whose pro-thrombotic risk depends on the presence and severity of hyperhomocysteinemia [23]. Similarly, the PAI-1 4G/4G genotype has a frequency of 29%, while the 4G/5G genotype is present in up to 50% of subjects, being only slightly more prevalent among individuals suffering from cerebrovascular events [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be recognized that none of the subjects were carriers for any mutations definitively associated with an increased pro-thrombotic risk (such as Factor II G20210A and Factor V G1691A) [23]. On the other hand, the genetic variants identified are not rare in the general population: the double heterozygosity (677 TC/1298 AC) of MTHFR has a frequency of about 34%, while the 1289 CC genotype is present in 9.4% of subjects [52], whose pro-thrombotic risk depends on the presence and severity of hyperhomocysteinemia [23]. Similarly, the PAI-1 4G/4G genotype has a frequency of 29%, while the 4G/5G genotype is present in up to 50% of subjects, being only slightly more prevalent among individuals suffering from cerebrovascular events [52].…”
Section: Discussionmentioning
confidence: 99%
“…Our population of healthy subjects had a similar allele frequency of the 5 tested SNPs to that reported in healthy subjects from Europe, Italy (Tuscany), and Campania [ 12 , 13 ], see Table S3 (Supplemental Material).…”
Section: Discussionmentioning
confidence: 57%
“…The prevalence of FV H1299R variant in Jordanian children with thrombotic events was found to be 25% and only 10% in the control group with a significant difference between the two groups. A recent study conducted in Southern Italy on 282 patients (adults and children) with ischemic stroke and 87 patients with transient ischemic attacks, revealed that the prevalence of FV H1299R was 9.9% in ischemic stroke group, 11.5% in transient ischemic attacks group and 9.1% in general population (Cernera et al, 2021). Importantly, it has been reported that the FV H1299R mutation increases the incidence of VT in FV Leiden mutation carriers (Faioni et al., 1999) and it was considered as a thrombotic risk factor itself (Alhenc-Gelas et al, 1999).…”
Section: Discussionmentioning
confidence: 97%